2017
DOI: 10.2147/copd.s140231
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of chronic bronchitic, emphysematous and ACOS phenotypes in COPD patients with frequent exacerbations

Abstract: PurposeChronic bronchitis (CB), emphysematous (EM) and asthma–chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS) phenotypes in COPD are well recognized. This study aimed to investigate distinguishing characteristics of these phenotypes in COPD patients with frequent exacerbations (FE).Patients and methodsA retrospective study was carried out. COPD patients with acute exacerbations were consecutively reviewed from November 2015 to October 2016. Patients were divided into FE and infrequent exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Seemungal et al and Mackay et al, respectively reported COPD patients with ≥ three exacerbations (SGRQ-c, p < 0.001) and ≥ two exacerbations (CAT, p = 0.025) per year have significantly worse HRQoL [ 33 , 37 ]. Cheng et al also reported COPD frequent exacerbators have significantly worse HRQoL (mMRC, p < 0.001; CAT, p < 0.001) compared to non-frequent exacerbators [ 38 ]. Therefore, this explains the significantly worse HRQoL among our patients with AE.…”
Section: Discussionmentioning
confidence: 99%
“…Seemungal et al and Mackay et al, respectively reported COPD patients with ≥ three exacerbations (SGRQ-c, p < 0.001) and ≥ two exacerbations (CAT, p = 0.025) per year have significantly worse HRQoL [ 33 , 37 ]. Cheng et al also reported COPD frequent exacerbators have significantly worse HRQoL (mMRC, p < 0.001; CAT, p < 0.001) compared to non-frequent exacerbators [ 38 ]. Therefore, this explains the significantly worse HRQoL among our patients with AE.…”
Section: Discussionmentioning
confidence: 99%
“…(33,37) Cheng et al also reported COPD frequent exacerbators have signi cantly worse HRQoL (mMRC, p < 0.001; CAT, p < 0.001) compared to non-frequent exacerbators. (38) Therefore, this explains the signi cantly worse HRQoL among our patients with AE. Despite similar exacerbation frequency, our patients with ACO had signi cantly worse HRQoL than those with NON-AE which highlights that COPD subtypes can also affect the patients' HRQoL.…”
Section: Discussionmentioning
confidence: 82%
“…The Spanish COPD Guidelines 19 describe four clinical phenotypes: ( i ) non-exacerbators, ( ii ) ACO, ( iii ) frequent exacerbators with emphysema, and ( iv ) frequent exacerbators with CB. Several differential characteristics were similarly described in frequent exacerbators of both emphysema and CB phenotypes compared to those of infrequent exacerbators 20 .…”
Section: Copd Phenotypesmentioning
confidence: 84%